A Review on the Fabrication of Polymer-Based Thermoelectric Materials and Fabrication Methods. (12th November 2013) - Kamarudin, Muhammad Akmal; Sahamir, Shahrir Razey; Datta, Robi Shankar; Long, Bui Duc; Mohd Sabri, Mohd Faizul; Mohd Said, Suhana
Abstract : Thermoelectricity, by converting heat energy directly into useable electricity, offers a promising technology to convert heat from solar energy and to recover waste heat from industrial sectors and automobile exhausts. In recent years, most of the efforts have been done on improving the thermoelectric efficiency using different approaches, that is, nanostructuring, doping, molecular rattling, and nanocomposite formation. The applications of thermoelectric polymers at low temperatures, especially conducting polymers, have shown various advantages such as easy and low cost of fabrication, light weight, and flexibility. In this review, we will focus on exploring new types of polymers and the effects of different structures, concentrations, and molecular weight on thermoelectric properties. Various strategies to improve the performance of thermoelectric materials will be discussed. In addition, a discussion on the fabrication of thermoelectric devices, especially suited to polymers, will also be given. Finally, we provide the challenge and the future of thermoelectric polymers, especially thermoelectric hybrid model.